Work, Professions, Their Organizations, Power and Criticism - Hurol Al, Yonca; Arslan, Adile (UCEAT Chamber of Architects, 1998)
The aim of this article is to describe the position of professional organizations in relation to power from a critical point of view.
This article was written in order to identify the critical position of professional organizations with respect to power. Because professional organizations are responsible to people.
Keywords: Profession, professional organization, power, criticism, building production